Food availability and long‐term predation risk interactively affect antipredator response. Issue 9 (22nd July 2021) - Shiratsuru, Shotaro; Majchrzak, Yasmine N.; Peers, Michael J. L.; Studd, Emily K.; Menzies, Allyson K.; Derbyshire, Rachael; Humphries, Murray M.; Krebs, Charles J.; Murray, Dennis L.; Boutin, Stan
Abstract: Food availability and temporal variation in predation risk are both important determinants of the magnitude of antipredator responses, but their effects have rarely been examined simultaneously, particularly in wild prey. Here, we determine how food availability and long‐term predation risk affect antipredator responses to acute predation risk by monitoring the foraging response of free‐ranging snowshoe hares ( Lepus americanus ) to an encounter with a Canada lynx ( Lynx canadensis ) in Yukon, Canada, over four winters (2015–2016 to 2018–2019). We examined how this response was influenced by natural variation in long‐term predation risk (2‐month mortality rate of hares) while providing some individuals with supplemental food. On average, snowshoe hares reduced foraging time up to 10 h after coming into close proximity (≤75 m) with lynx, and reduced foraging time an average of 15.28 ± 7.08 min per lynx encounter. Hares tended to respond more strongly when the distance to lynx was shorter. More importantly, the magnitude of hares' antipredator response to a lynx encounter was affected by the interaction between food‐supplementation and long‐term predation risk. Food‐supplemented hares reduced foraging time more than control hares after a lynx encounter under low long‐term risk, but decreased the magnitude of the response as long‐term risk increased. In contrast, control hares increased the magnitude of their response as long‐term risk increased. Our findings show that food availability and long‐term predation risk interactively drive the magnitude of reactive antipredator response to acute predation risk. Determining the factors driving the magnitude of antipredator responses would contribute to a better understanding of the indirect effects of predators on prey populations.